دراسة تسربات النفط الخام وحرق الغاز المصاحب فـي بيئة حقل الناصرية النفطي جنوب العراق - عريبي الدخيليمحسن; هديرس نعيثلعيسى (University of Thi-Qar Journal of Science, 2019)
The” current study involves the use of The device utilizes to measure concentration, and identification of origin, and distribution of Polycyclic Aromatic Hydrocarbons in the soil, depths of laminar water well column, and groundwater by high performance liquid chromatography device which contains at high precision separation techniques, within the Nasiriyah oilfield, for the period of October2015 until September 2016. This study is based on the compounds of Polycyclic Aromatic Hydrocarbons which can penetrate from surface soil into groundwater across different layers. Moreover, it depends on following the change in concentrations of these compounds and its associated elements are used as a means to track the descent of these materials into the groundwater. The change in concentrations which were taken at different distances (0,35,70,210,420,630) meters from the "source of contamination, the concentrations of Polycyclic Aromatic Hydrocarbons(PAHs) in the soil ranged between (0.003) µg/Kg at station six PS6 and (73.462) µg/Kg at station one PS1, In addition, there are another samples were taken at different depths, such as (10, 20, 30, 40, 50, 60) meters along the well column ranged between(0.303) µg/Kg When depth 50 meters and(1.072) µg/Kg When the soil surface, and this was a way to find a type of comparison between the change of concentration and distance. The “compounds’ source of PAHs into the soil and groundwater is common between Pyrogenic and Petrogenic. This fact is because of two reasons, first one is that the ratio of compounds PAHs which consists of low molecular weights to the high one is less than number 1. Also, the ratio of compounds Phenanthrene to Anthracene and the presence of high concentrations from compounds Pyrene and Anthracene, all of these evidences refer to sources of Pyrogenic. On the other hand, the ratio between Flouranthene to Pyrene” compounds are larger than number 1. In addition, presence of naphthalene compounds with Flourene and Phenanthrene are evidences on sources of Petrogenic. تضمـنت الدراسة الحالية قياس تركيز وتحديد أصل وتوزيع المركبات الهيدروكربونية الأروماتية متعددة الأنوية (PAHs) باستخدام جهاز كروماتوغرافـيا السائل عالي الاداء HPLC بتقنيات فصل عالية الدقة، لعينات مأخوذة مـن ترب سطحية واخرى لأعماق مختلفة مـن عمود الطباقي للبئر المائي ومياه جوفـية ضمـن حقل الناصرية النفطي للفترة مـن تشرين الأول 2015 الـى أيلول 2016. اذ استندت هـذه الدراسة الـى أن مركبات PAHs يمكن ان تتسرب مـن التـربة السطحية الـى المياه الجوفـية عبر الطبقات المختلفة بمتابعة تغير تراكيز تلك المركبات كوسيلة لتعقب مسار هجرة تلك المركبات افقيا وعموديا الـى مـنطقة بئر الماء مـن خلال عينات التـربة الافقية التي أخذت عـلى مسافات (0,35,70,210,420,630) متر مـن مصدر التلوث، اذ تراوح مـعدل تركيز مركبات PAHs فـي التـربة بـين µg/Kg )0.003) فـي المحطة السادسة PS6 الـى µg/Kg )73.462) فـي المحطة الأولى PS1. وعينات أخرى عمودية مـن الأعماق (0,10,20,30,40,50,60) متر عـلى طول عمود البئر اذ تراوح مـعدل التركيز بـين 0.303) µg/Kg) عـند العمق)50( متر الـى (1.072) µg/Kg عـند سطح التـربة بمحاولة لإيجاد نوع مـن العلاقة بـين تغير التركيز والمسافة. إن مصدر مركبات PAHs فـي التـربة والمياه الجوفـية هو مشترك Pyrogenic وPetrogenic لأن نسبة مركبات PAHs ذات الأوزان الجزيئية الواطئة الـى العالية أقل مـن العدد (1) ونسبة مركبات Phenanthrene الـى Anthracene ووجود مركبات Pyrene وAnthracene بتراكيز عالية يشير الـى مصادر Pyrogenic فـيما كانت نسبة مركب Flouranthene الـى Pyrene أكبرمـن العدد (1) ووجود مركبات Naphthalene مـعFlourene و Phenanthrene والتي تشير الـى مصادر Petrogenic. الكلمات المفتاحية: المركبات الأروماتية متعددة الأنوية، حقل الناصرية النفطي، كروماتوغرافـيا السائل عالي الأداء.